Bone morphogenetic protein-9 promotes the proliferation of non-small cell lung cancer cells by activating PI3K/Akt and Smad1/5 pathways. Issue 12 (19th February 2020) - Hou, Xiaodong; Peng, Yuanbo; Liu, Jianhua; Zhong, Qixiang; Yu, Zhenglun; Zhang, Lei
Abstract : Non-small-cell lung carcinoma (NSCLC) is any type of epithelial lung cancer other than small cell lung carcinoma (SCLC), which accounts for about 85% of all lung cancers. Abstract : Non-small-cell lung carcinoma (NSCLC) is any type of epithelial lung cancer other than small cell lung carcinoma (SCLC), which accounts for about 85% of all lung cancers. Bone morphogenetic protein (BMP)-9 in humans is encoded by the growth differentiation factor 2 gene, which belongs to the transforming growth factor-beta superfamily. In the present study, we explored the role of BMP-9 in A549 and NCI-H1650 cell proliferation and its possible molecular mechanisms. 25 NSCLC patients were recruited to evaluate mRNA expression of BMP-9 to determine its clinicopathologic significance. We found that recombinant protein BMP-9 and overexpression of BMP-9 promoted A549 and NCI-H1650 cell proliferation in vitro, which was abolished by phosphatidylinositol 3-kinase (PI3K) inhibitor (LY294002). Western blot results revealed that BMP-9 significantly activated the PI3K/Akt and Smad1/5 pathway signaling. In vivo, BMP-9 promoted tumor growth and PI3K/Akt and Smad1/5 signaling pathways in an A549 or NCI-H1650 cell line-derived xenograft model. Knockdown BMP-9 or BMP-9 receptor ALK1 inhibited A549 cell growth in vitro and in vivo, which was associated with regulating the PI3K/Akt and Smad1/5 signaling pathways. These results demonstrated that BMP-9 promoted A549 and NCI-H1650 cell proliferation via PI3K/Akt and Smad1/5 signaling pathways.